Paramagnetic defects in CVD diamonds - Talbot-Ponsonby, D; Daniel Talbot-Ponsonby (1997)
﻿ Paramagnetic defects in free standing polycrystalline diamond films made by chemical vapour deposition (CVD) have been studied using electron paramagnetic resonance (EPR), electron-nuclear double resonance (ENDOR) and infrared absorption. EPR experiments at a range of frequencies (1-35 GHz) confirm the 1H hyperfine parameters for the recently identified H1 defect (Zhou et al., Phys. Rev. B, 54:7881 (1996)). In the samples studied here, H1 is always accompanied by another defect at g=2.0028(1). Saturation recovery measurements are consistent with two defects centred on g=2.0028. The spin-lattice relaxation rate of H1 is a factor of 10-100 times more rapid than the single substitutional nitrogen centre (N0S), which is known to be incorporated into the bulk diamond. 1H matrix ENDOR measurements indicate that the H1 centre is in an environment with hydrogen atoms 2-10 A distant from the centre. The near neighbour hydrogen identified by the EPR was not detected in the ENDOR experiments. The concentration of H1 correlates with the total integrated C-H stretch absorption in the samples studied here. All the evidence is consistent with H1 being located at hydrogen decorated grain boundaries (or in intergranular material) rather than in the bulk diamond. The affect of annealing the films in vacuo up to 1900 K has been studied. On annealing at 1700 K it was found that some of the hydrogen on internal grain boundaries became mobile but was not lost from the sample, and the intensity of the EPR absorption at g=2.0028 decreased. Annealing at 1900 K severely degraded the optical properties of the samples, and a new defect with g=2.0035(2) was created. Infrared measurements show that hydrogen is lost from most CVD diamond samples when annealed to 1900 K for four hours. An EPR imaging (EPRI) probe was designed and built. This comprised a 3-loop, 2-gap loop-gap resonator and a pair of anti-Helmholtz coils providing a magnetic field gradient ∂Bz/∂z. Using this probe the distribution of N0S was measured in the growth direction of four CVD diamonds to a resolution of 20 μm. The distribution of N0S is shown to be different to the distribution of defects with g=2.0028. Two-dimensional images of the spin density of N0S in single crystal type Ib diamonds made by the high temperature and pressure (HTP) method have been generated, demonstrating a resolution of 100 μm. A two-dimensional image of the spin density of g=2.0028 defects in a CVD sample is compared to a photograph of the same sample, showing the correlation between the distribution of the defects with the distribution of non-diamond material in the sample. The distribution of the [N-N]+ defect in a natural diamond has been examined using ∂Bz/∂Bϰ field gradient coils.